Generous Forgiveness; (Analysis of What is " Forgiveness" in the Qur'an, Emphasizing the View of Allameh Javadi Amoli) - Ali Modaber (اخلاق وحیانی)
"Al-Safh" (Forgiveness) is one of the teachings of Islamic society that the Holy Quran has invited in several verses. However, some scholars and commentators have considered "al-Safh" and "al-Afv" to be synonymous (meaning forgiveness;( According to some other lexicographers and commentators, including Allameh Javadi Amoli, the "al-Safh" described in the Holy Quran and the narrations of the Ahl al-Bayt (as) as "beautiful" has a different meaning from "al-Afv"  and is superior to it. It arises from a special inner dignity, because "al-Afv" means abandoning revenge; But the al-Safh means abandoning the principle of criminality, removing resentment and unhappiness from the heart, and graciously forgiving and not seeing a page of one's own memories - on which the error and aggression of others are involved - and ignoring it and opening a beautiful page and forgetting the mistake of the wrongdoer, the effects of which are not only leaving revenge, but also leaving blame of the wrongdoer. Evidences of the second view are: specifying some words of scholars and dictionaries, coordination of the literal meaning of the term with the technical meaning, Quranic witnesses, witnesses of the narration and opinions of commentators, especially commentators of literature. In this article, after introductory discussions, these evidences are examined in detail.